Pengembangan Motor IoT untuk Pemantauan Kecepatan dan Pemeliharaan Melalui Telegram - Pranata, Rangga; Styawati, Styawati (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
This research focuses on developing Motor IoT as an advanced solution for real-time motor speed monitoring and maintenance notifications via Telegram. The research method includes installing a magnetic sensor on the motor to measure wheel rotation and produce accurate speed data. The data is sent to the IoT platform and integrated with Telegram, providing users with speed monitoring information as well as providing timely maintenance notifications. In addition, this system monitors the overall condition of the motorbike. The results of research and testing show that Motor IoT can be used and applied to motorized vehicles with the ability to provide accurate information and efficient maintenance notifications. The use of IoT and Telegram technology provides an effective solution for monitoring motor performance, optimizing maintenance and reducing potential damage. IoT motorbikes not only increase the efficiency of using motorized vehicles, but also contribute to minimizing the risk of damage and increasing the overall service life of motorbikes. In addition, the magnetic sensor was successfully integrated with the motor monitoring and maintenance system via Telegram, providing appropriate responses to predetermined conditions. This system is also able to send notifications to Telegram when the motorbike is started, providing information on the distance traveled by the user, with reminders to change the oil every 1000 kilometers. This research produces innovations that can have a positive impact on the automotive industry and user welfare.